Influence of SLM on shape memory and compression behaviour of NiTi scaffolds. Issue 1 (2015) - Dadbakhsh, Sasan; Speirs, Mathew; Kruth, Jean-Pierre; Van Humbeeck, Jan
Abstract: Octahedron-shaped porous scaffolds made from shape memory nickel–titanium (NiTi) were manufactured with different solid volume fractions using selective laser melting (SLM). Various SLM parameters were selected to affect the mechanical behaviour and shape memory response. It was shown that high laser power with high scanning speed (HP) parameters reduced the martensitic transformation temperatures as compared to low laser power low scanning speed (LP) parameters, resulting in an increased pseudoelastic behaviour (due to presence of austenite at room temperature). HP parameters, however, led to a larger geometrical mismatch with the original design and a higher solid volume fraction. The compression behaviours were also analysed and exhibited in correlation with the volume fractions.